Соціальна політика в Україні - Ткаченко, Надія Марківна (My University, 2011)
Досліджено стратегічні напрями соціальної політики в Україні, проведено аналіз сфери соціального сектору Державного комітету статистики України; досліджено проблемні питання пов’язані з тривалістю відпусток громадянам України, методикою обчислення середньої заробітної плати; методику нарахування допомоги з тимчасової непрацездатності. Strategic directions of social policy are investigational in Ukraine, the analysis of sphere is conducted social to the sector of the State committee of statistics of Ukraine; problem questions are investigational related to duration of vacations to the citizens of Ukraine, by methodology of calculation of middle salary; methodology of extra charge of help from temporal nonoperability.
Keywords: соціальна політика; Закони України; середня заробітна плата; соціальний сектор; відпустки; social policy; Laws of Ukraine; middle salary; social sector; vacations hospital; methodology; кафедра обліку і аудиту